Excessive fructose intake inhibits skeletal development in adolescent rats via gut microbiota and energy metabolism - Gao, Tianlin; Tian, Chunyan; Tian, Ge; Ma, Li; Xu, Lili; Liu, Wendong; Cai, Jing; Zhong, Feng; Zhang, Huaqi; Ma, Aiguo (Frontiers in Microbiology, 2022)
Excessive fructose intake from dessert and beverage may influence the bone development among adolescents. The gut microbiota (GM) and energy metabolism play important roles in bone development. In this study, 40 female adolescent rats were randomly assigned to the control group, the fructose groups with two concentrations and the glucose group as the positive control group. After 10 weeks, Serum glucose and lipids were detected by means of an automatic analyser and the bone microstructure was analyzed by Micro-CT. Then, the GM were determined via 16S rRNA sequencing analysis and energy metabolism was detected by measuring serum carbohydrate metabolites. At last, bone metabolism markers were measured via ELISA kits. The results showed that excessive fructose intake could increase the body weight and influence the glucolipid metabolism of female adolescent rats. Meanwhile, the bone microstructures were impaired with excessive fructose intake. Mechanistically, excessive fructose intake shifted the GM of rats with the decrease of Lachnospiraceae, Ruminococcaceae and increase of Allobaculum, Lachnospiraceae. Energy metabolism analysis suggested that most metabolites of fructose did not enter the tricarboxylic acid cycle to provide energy for the body development. Furthermore, serum bone metabolism markers showed that excessive fructose intake could decrease both bone formation and resorption. Our results suggested that excessive fructose intake could inhibit the skeletal development in adolescents. One potential mechanism might be that it affected the intestinal microbiota homeostasis in the juvenile body, thus changing the energy metabolism level, and ultimately affecting the bone metabolic balance.